2022
DOI: 10.3389/fgene.2022.849016
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study for Yield and Yield-Related Traits in Diverse Blackgram Panel (Vigna mungo L. Hepper) Reveals Novel Putative Alleles for Future Breeding Programs

Abstract: Blackgram (Vigna mungo L. Hepper) is an important tropical and sub-tropical short-duration legume that is rich in dietary protein and micronutrients. Producing high-yielding blackgram varieties is hampered by insufficient genetic variability, absence of suitable ideotypes, low harvest index and susceptibility to biotic-abiotic stresses. Seed yield, a complex trait resulting from the expression and interaction of multiple genes, necessitates the evaluation of diverse germplasm for the identification of novel yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 105 publications
(115 reference statements)
0
10
1
Order By: Relevance
“…The current study compared the locations of the QTLs for the flowering time detected in the current study with the candidate gene LOC106774489 at the Q.DtF.10 and found that the QTLs were located on the CN80 reference chromosomes 2, 4, 5, 6, 8 and 9, while LOC106774489 was on the CN80 reference chromosome 7. Thus, none of the QTLs detected in the current study matched the Q.DtF.10 identified by Singh et al (2022). However, notably, none of the flowering QTLs were common in the F2BGA and F2BGB populations, albeit the two populations shared the same cultivated parent, CN80.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…The current study compared the locations of the QTLs for the flowering time detected in the current study with the candidate gene LOC106774489 at the Q.DtF.10 and found that the QTLs were located on the CN80 reference chromosomes 2, 4, 5, 6, 8 and 9, while LOC106774489 was on the CN80 reference chromosome 7. Thus, none of the QTLs detected in the current study matched the Q.DtF.10 identified by Singh et al (2022). However, notably, none of the flowering QTLs were common in the F2BGA and F2BGB populations, albeit the two populations shared the same cultivated parent, CN80.…”
Section: Discussionmentioning
confidence: 45%
“…These clearly indicated that days to flowering in black gram is a polygenic trait. The difference in the number of the QTLs for flowering detected in the current study and that in Singh et al (2022) may be due principally to: 1) differences in the methods of QTL mapping (genome-wide association versus linkage-based QTL analysis); and 2) differences in flowering time traits (days to 50% flowering and days to first flowering). The current study compared the locations of the QTLs for the flowering time detected in the current study with the candidate gene LOC106774489 at the Q.DtF.10 and found that the QTLs were located on the CN80 reference chromosomes 2, 4, 5, 6, 8 and 9, while LOC106774489 was on the CN80 reference chromosome 7.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations